Participatory Assessment of Ecosystem Services from Community-Managed Planted Forests in Bhutan - Rai, P.B.; Sears, R.R.; Dukpa, D.; Phuntsho, S.; Artati, Y.; Baral, H. (MDPI, 2020)
Planted forests provide a range of ecosystem services, from the local to global scales. In this study, we evaluated the perceptions by local people of the ecosystem services from planted forest stands in Bhutan. We employed household questionnaires, interviews and focus group discussions in eight villages in two regions of Bhutan: Trashigang dzongkhag, in eastern Bhutan, and Punakha dzongkhag in western Bhutan. At all sites, the planted forests were created several decades ago to restore forest cover in deforested and degraded areas. The restored stands were perceived by residents to provide multiple goods and ecosystem services important to local security, health, and livelihoods, including wild edibles, freshwater, and soil protection, and aesthetic and cultural services. This study indicates that local community participation in forest resource management can ease user conflict and manage the planted forests sustainably. We see community-based forest restoration on degraded lands as a viable approach, among others, to achieve national commitments to the Bonn Challenge and other multilateral environmental agreements related to forests.